Motivation of behavior of elementary school children with auditory sensory deprivation - Yakovleva, Svitlana (Social Welfare: Interdisciplinary Approach, 2013)
This paper presents an experimental study of motivation of behavior of elementary school children with auditory sensory deprivation. Hard-of-hearing children with 2-4 degree of deafness were examined in accordance with the strength of their nervous processes. We used the table of behavior features proposed by Гильбух (2009) and a questionnaire to evaluate motivation to attend school. The paper presents correlations between indicators of behavioral responses and motivational sphere for this children’s group according to their strength of nerve processes before schooling start, during school studying and at additional correction implementation. Influence of schooling and additional correction on formation of new correlative relationships was shown, this fact highlighting impact of schooling and additional correction on neural process activation that significantly improves the learning activity states.